Colonoscopic Perforations - Rai, Vinay; Mishra, Nitin (Clinics in Colon and Rectal Surgery, 2018)
Colonoscopy is the gold standard for colon cancer screening. It has led to a decrease in the incidence of colorectal cancer mortality. Colon perforation is a feared complication of this procedure with high morbidity and substantial mortality. Due to the high volume of colonoscopies performed, the absolute number of colonoscopic perforations is relatively high. It leads to a substantial cost to the patient and the health system. Understanding the mechanisms and the risk factors may help in preventing perforation. Traditionally, a laparotomy with creation of a stoma was used to address this complication. However, minimally invasive techniques such as laparoscopy and endoluminal repairs are being used more commonly now. More surgeons are favoring primary anastomosis (with or without a diverting loop ileostomy) than a Hartmann procedure.
Keywords: colonoscopy; perforation; complication; screening